2015
DOI: 10.5114/pwki.2015.54011
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of bleeding scores for patients presenting with myocardial infarction: a meta-analysis of 9 studies and 13 759 patients

Abstract: IntroductionDue to its negative impact on prognosis, a clear assessment of bleeding risk for patients presenting with acute coronary syndrome (ACS) remains crucial. Different risk scores have been proposed and compared, although with inconsistent results.AimWe performed a meta-analysis to evaluate the accuracy of different bleeding risk scores for ACS patients.Material and methodsAll studies externally validating risk scores for bleeding for patients presenting with ACS were included in the present review. Acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 40 publications
1
11
0
3
Order By: Relevance
“…However, the performance of the ACEF score itself in the context of non-ischemic events in ACS, especially in patients treated conservatively during the index hospital stay, has not been previously tested. The observed AUC of 0.72 for bleeding requiring blood transfusion seems to be comparable to the values reported for other bleeding risk scores [ 15 ], but it should be confirmed in other cohorts. The ACEF score may have a limited value for the selection of patients with the highest benefit of an invasive strategy in patients with non-ST-segment ACS, as symptoms of the ongoing ischemia and/or haemodynamic instability may be more important for the decision-making process.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…However, the performance of the ACEF score itself in the context of non-ischemic events in ACS, especially in patients treated conservatively during the index hospital stay, has not been previously tested. The observed AUC of 0.72 for bleeding requiring blood transfusion seems to be comparable to the values reported for other bleeding risk scores [ 15 ], but it should be confirmed in other cohorts. The ACEF score may have a limited value for the selection of patients with the highest benefit of an invasive strategy in patients with non-ST-segment ACS, as symptoms of the ongoing ischemia and/or haemodynamic instability may be more important for the decision-making process.…”
Section: Discussionsupporting
confidence: 79%
“…These findings were somewhat expected, as two of three components of the ACEF score, i.e. age and serum creatinine level, are strong predictors of ischemic and bleeding events in the setting of ACS [ 1 , 2 , 15 , 16 ]. However, the performance of the ACEF score itself in the context of non-ischemic events in ACS, especially in patients treated conservatively during the index hospital stay, has not been previously tested.…”
Section: Discussionmentioning
confidence: 82%
“…The HAS-BLED score is another system that, although it is intended to assess the risk of bleeding in patients with atrial fibrillation treated with anticoagulants, is particularly useful in patients with acute coronary syndrome (ACS) (Pisters et al 2010) It is easy to administer and includes important variables such as alcohol use, liver dysfunction, and a previous history of bleeding. (Hsieh et al 2015;Taha et al 2015) The authors of the PRECISE-DAPT score use individualized data from eight randomized controlled trials to develop a hemorrhagic risk assessment system that determines the duration of DAPT in patients who have indications to receive such therapy. Compared to previous scores, the PRECISE-DAPT score is the only that offers long-term stratification of bleeding risk and also takes into account the variable "prior bleeding", which weighs four times more than other variables in the assessment.…”
Section: Bleeding Risk Assessment Scoresmentioning
confidence: 99%
“…A comprehensive assessment revealed minor differences in the results, and a meta-analysis also suggested that ACTION, CRUSADE, and ACUITY-HORIZONS similarly performed while predicting the risk of bleeding in patients with AMI. 10) Initially, all these RS systems were developed in patient cohorts in whom the femoral approach was predominantly used, and none has been confirmed for the use with the radial approach, which now constitutes the recommended access site in coronary angiography and PCI for AMI. 6) In this study, we observed that the ACUITY-HORIZONS RS performed better than the CRUSADE and ACTION systems in terms of the predictive ability for 30day major bleeding, although Abu-Assi, et al reported the CRUSADE score as the most accurate quantitative tool for predicting bleeding during hospitalization in patients with NSTEACS and STEMI compared with the ACTION and ACUITY-HORIZONS scores.…”
Section: Comparison Of Rsmentioning
confidence: 99%